Economic Policy Formulation Risks to Existence Rural Creative Industry as a Form of Resilience Legal Protection - Dewa Gede Sudika Mangku; Ni Putu Rai Yuliartini; Ni Ketut Sari Adnyani (University of Udayana, 2022)
The purpose of this research is to find out, among others: (1) the development of the creative industry rural areas in Buleleng district in their resilience to the Covid 19 Pandemic; (2) the obstacles faced by the rural creative industry in the Covid-19 Pandemic situation; (3) Strategy in the form of economic policy formulation rises to the existence of the creative industry rural areas as a form of resilience in the legal protection of Small and medium-sized enterprises, in the face of a pandemic Covid 19 in Buleleng Regency. This research is an empirical juridical research with nature with the field of public policy studies. This sociolegal research uses a socio-economic approach referring to laws and regulations relating to the economic development of rural areas and Small Industry, a conceptual approach, and a case approach. Technique research analysis is a legal hermeneutic technique which is presented in a qualitative descriptive manner. The results of the study indicate that it is important for the government to assist in restoring and revitalizing the rural creative industry in Buleleng Regency with various government assistance and policies that can support Small Industry businesses. A total of 1,785 cooperatives and 163,713 micro, small and medium enterprises were affected by the coronavirus (Covid-19) pandemic. Strategy The government's policy is divided into various short, medium and longterm strategies, including short term and urgent, the government focuses on reducing the addition of COVID-19 fatalities with an emphasis on health sector stimulus and welfare assistance for the affected people.